Wettability Alteration During Low Salinity Water Flooding in Carbonate Reservoirs: An Experimental and Theoretical Study - Sari, Ahmad (Curtin University, 2020)
The aim of this research is to achieve a more comprehensive understanding of the underlying mechanisms of Low Salinity Effect in carbonate reservoirs through systematic analysis of physical, chemical, and geochemical factors that affect the oil-brine-carbonate interactions during low salinity waterflooding. This research presents several hypotheses and suitable strategies for validating these hypotheses to fill the knowledge gaps that were identified in the literature. The outcome of this research can have significant implications for field application of LSWF.